Immune cell proportions correlate with clinicogenomic features and ex vivo drug responses in acute myeloid leukemia - Romine, Kyle A.; Bottomly, Daniel; Yashar, William; Long, Nicola; Viehdorfer, Matthew; McWeeney, Shannon K.; Tyner, Jeffrey W. (Frontiers in Oncology, 2023)
The implementation of small-molecule and immunotherapies in acute myeloid leukemia (AML) has been challenging due to genetic and epigenetic variability amongst patients. There are many potential mechanisms by which immune cells could influence small-molecule or immunotherapy responses, yet, this area remains understudied. Here we performed cell type enrichment analysis from over 560 AML patient bone marrow and peripheral blood samples from the Beat AML dataset to describe the functional immune landscape of AML. We identify multiple cell types that significantly correlate with AML clinical and genetic features, and we also observe significant correlations of immune cell proportions with ex vivo small-molecule and immunotherapy responses. Additionally, we generated a signature of terminally exhausted T cells (Tex) and identified AML with high monocytic proportions as strongly correlating with increased proportions of these immunosuppressive T cells. Our work, which is accessible through a new cell types module in our visualization platform (Vizome; http://vizome.org/aml2), can be leveraged to investigate potential contributions of different immune cells on many facets of the biology of AML.